Preschool or Prep School? Rethinking the Role of Early Years Education. (June 2014) - Ang, Lynn
Governments around the world continue to grapple with issues relating to how preschool services should be delivered, what type of provision is most appropriate, and for what purpose. These issues are particularly pertinent in a fast evolving early years sector such as the United Kingdom and many parts of the world where early years education has become a highly political topic. This article argues that given current emphasis on 'school readiness' and the formalisation of children's learning in England and internationally, tensions remain about the role of early years education and what it entails — as a nexus for enriching children's lives and learning experiences, or simply preparing children for schooling. Building on Genishi's work on rethinking dominant values of early years education and respecting the importance of inclusion and diversity, the discussion explores debates around assessment, pedagogy and the curriculum in supporting children's learning and how these are deeply embedded in wider societal values. The article calls for a rethinking of the role of early years education — the values, choices, and judgements that societies make which inform children's learning and the contexts in which they learn.